ANALYSIS OF CIVIL SERVANT SALARIES AS COMMON PROPERTY AFTER DIVORCE - Muhammad Ilham (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2025)
This study aims to examine the rights and obligations of husbands and wives who are civil servants (PNS) in the event of divorce according to Marriage Law No. 1 of 1974 and regulations related to joint property. The background of this research is based on the fact that divorce, although a last resort in a marriage, often causes serious problems, especially regarding the division of joint property and social implications, particularly for couples who are civil servants due to the existence of special employment regulations. The urgency of this research lies in the need to understand the legal protection for wives and children after divorce so that their rights are not violated. The method used is normative juridical research with a qualitative approach, combining law in book and law in action analysis through a review of legislation and Islamic legal literature. The results of the study show that divorce among civil servants has specific legal consequences, including the obligation of the husband to give part of his salary to his ex-wife and children if the divorce is at his request, while this right is forfeited if the wife files for divorce or remarries. This study recommends the need for more intensive dissemination of information regarding the rules on marriage and divorce for civil servants, as well as improved legal protection to prevent inequality of rights between the divorcing partie